Delving into the ‘why, what, and what for’ of digital technology use in physical education - Saiz-González, Pablo; Sierra-Díaz, Jacob; Cecchini, Jose Antonio; Fernandez-Rio, Javier (Education and information technologies, 2025)
The use of digital technologies is a reality in the educational context. Smart boards, computers, laptops, tablets or internet connection are frequently used in education. In physical education (PE), the use of digital technology is also gaining traction. However, little is still known about which digital technologies are being used, why they are being used, and how they are being used. Thus, the purpose of this study was to use a qualitative cross-sectional research design based on a web-based survey study where participants self-reported their responses to answer this question. Completed surveys were returned by 213 PE teachers (71 females and 142 males, ages 23–66, M = 41.47 years). Six technological tools were identified as the most used in PE: apps, smartphones/tablets, speakers, smartwatches, stopwatches, and exergames. Furthermore, the results showed that most participants used digital technology mainly to improve and streamline their teaching (scheduling, time management, assessment and grading, recording videos, playing music, and sending tasks). However, they also used it to teach specific content, to support the transfer of knowledge to the daily lives of the students and as a resource for students’ work. Despite the unique challenges of the subject, some teachers are leading the way for digital technology use in PE. The experiences of the participants in this study could be useful for other teachers considering the use of digital technology in their lessons.